Modelling understorey pasture production in a hortipastoral system - Khan, T.A.; Kumar, Sunil (Indian Journal of Agroforestry, 2020)
Secondary data of ten-year tree-growth and understorey pasture production in an Aonla (Emblica officinalis) + Dicanthium annulatuml Panicum maximum have been used for modelling the understorey pasture as affected by tree-crown area. Three more year data from the same system and understorey pasture (Panicum maximum) along with PAR and soil moisture and tree roots have been used and predictive assessment of pasture production for 25 years. It has been obtained that the function, Crown area (m2) = 8.802-4.500 (CD-cm) +0.616 (CD)2 was the best fit for tree-crown growth estimation and could explain 98.4% variation in the estimated values. Curve estimation indicates the appropriateness of Cubic function (P<0.01) and could explained 22.5% variation in the estimated values. Integration of crown area growth-model with understorey pasture production model shows that, through such effort, understorey pasture can be estimated over the system growth and save the future cost of experimentation at a specific location.